Studies of Equilibria Involving the Binary and Ternary Complexes of Aluminium with Eriochrome Cyanine R (ECR) and Cetylpyridinium Chloride (CP) - Ahmad, Musa; Narayanaswamy, Ramaier (Universiti Putra Malaysia Press, 2005)
This paper is concerned with the study of stoichiometry of binary (aluminiumECR) and ternary (aluminium-ECR-CP) complexes of aluminium. Both complexes are shown to be present in the solution and in equilibrium with each other. The formation constant, the reaction rate and the stoichiometry of both complexes have been evaluated and a possible reaction mechanism of the ternary complex formation is proposed in this paper.